2008
DOI: 10.1161/atvbaha.108.163931
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Differences in the Kinetics of Nonfasting TRL, IDL, and LDL Apolipoprotein B-100 in Men and Premenopausal Women

Abstract: Objective-To investigate mechanisms underlying gender differences in serum lipoprotein concentrations, the kinetic behavior of apoB-100 was assessed. Methods and Results-Twenty subjects (Ͻ50 years; 12 men and 8 premenopausal women) were provided a Western diet for 4 to 6 weeks, after which the kinetics of apoB-100 in triglyceride-rich, intermediate-density, and low-density lipoprotein (TRL, IDL, and LDL) were determined in the fed state. Nonfasting plasma TC, LDL-C, and triglyceride concentrations were 23%, 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 50 publications
3
38
1
Order By: Relevance
“…Previous studies have suggested that the postmenopausal state in women is associated with higher plasma LDL-C, VLDL, TG, apo (B) and lower HDL-C concentrations than premenopausal women of comparable age [41,42]. However, we did not found any study addressing the question whether menopausal status has any effect on serum Lp(a) levels in patients with diabetes or not.…”
Section: Discussioncontrasting
confidence: 71%
“…Previous studies have suggested that the postmenopausal state in women is associated with higher plasma LDL-C, VLDL, TG, apo (B) and lower HDL-C concentrations than premenopausal women of comparable age [41,42]. However, we did not found any study addressing the question whether menopausal status has any effect on serum Lp(a) levels in patients with diabetes or not.…”
Section: Discussioncontrasting
confidence: 71%
“…Possibly our results suggest that similar mediators affect the postprandial ATBF response. The greater plasma NEFA and lower TG concentrations that we found in women compared with men are to be expected from other studies; greater NEFA concentrations may relate to greater fat mass in women [37] and lower TG concentrations to faster removal [38,39]. We did not find a gender difference in ATBF, so this is unlikely to have contributed.…”
Section: Table 3 Univariate Inter-relationships Between Atbf Bmi Andsupporting
confidence: 67%
“…Data for 10 age- and sex-match healthy controls were available from a previous study 17 ; the methods applied for determination of kinetic parameters were similar to this study. Exclusion criteria were chronic illness including endocrine, hepatic, renal, thyroid or cardiac dysfunction, smoking, consumption of ≥2 alcoholic drinks per day, and current use of medications known to affect lipid metabolism (lipid lowering drugs, fish-oil capsules, β blockers or diuretics).…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the controlled dietary phase, a primed, constant infusion of deuterated-leucine (5,5,5- 2 H 3 -L-leucine; Cambridge Isotope Laboratories, Andover, MA) was administered intravenously in the fed state to determine the kinetics of apoB-100 containing lipoproteins, as previously described 17 . In brief, following a 12-hour overnight fast, subjects were provided with the experimental meal on an hourly basis for 20 hours.…”
Section: Methodsmentioning
confidence: 99%